Cell-Free Supernatant Obtained From a Salt Tolerant Bacillus amyloliquefaciens Strain Enhances Germination and Radicle Length Under NaCl Stressed and Optimal Conditions - Naamala, Judith; Msimbira, Levini A.; Antar, Mohammed; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2022)
Seed germination and early plant growth are key stages in plant development that are, susceptible to salinity stress. Salinity is currently a major global constraint to crop production, affecting all stages of growth and development of many crop plants. Plant growth promoting microorganisms (PGPMs) have been reported to produce substances, in their growth media, that could enhance plant growth under more optimal conditions, and or mitigate abiotic stresses, such as salinity. However, when exposed to significant levels of salt, PGPMs could lose their ability to produce plant growth promoting substances. Salt tolerant strains, however, might retain their ability to produce plant growth promoting substances, even when exposed to significant levels of salt. This study was carried out to elucidate the ability of a NaCl tolerant Bacillus amyloliquefaciens strain’s cell-free supernatant to enhance germination and radicle length of corn, soybean and tomato, under optimal and NaCl stressed growth conditions. NaCl levels of 0, 50 and 75 mM, and cell-free supernatant dilutions of 1:100, 1:500, 1:750 and 1:1000, were used for the study. Ten seeds were placed on a Petri plate lined with filter paper. Petri plates with seeds were then randomly allocated to the treatments and placed in a germination chamber, in the dark, in a completely randomised design. Data on percentage germination was collected every after 24 h for 72 h while data on radicle length were collected after seven days. SAS proc mixed was used to analyze the data, at 5 % significance level. Results showed that, the effect of the cell-free supernatant on mean percentage germination and mean radicle length varied across concentrations, plant species and NaCl levels. For instance, concentrations of 1:500, 1:750 and 1:1000, of the cell free supernatant, enhanced radicle length of soybean under normal conditions, while dilutions of 1:500 and 1:750 enhanced radicle length of corn exposed to 50 mM NaCl. Results showed that Bacillus amyloliquefaciens EB2003A produces in its growth media, substances that enhance mean percentage germination and mean radicle length in soybean and corn, under stressed and or unstressed conditions.